Metrics of sustainable diets and food systems - Bioversity International & CIHEAM-IAMM Workshop Report. November 4-5, 2014, Montpellier, France - Allen, T.; Prosperi, P. (2014)
The three main objectives of the workshop: 1- Establish a multidisciplinary task force of experts. Joint effort is key to advance on the agenda on the metrics of sustainable diets and food systems. The organizing team would like to promote future personal and institutional cooperation in the field of sustainability analysis and assessment of the food systems and encourage project oriented co-operations. 2- Explore the different approaches to assess the sustainability of diets and food systems. It is also broadly expected that the symposium and workshop will be an opportunity for the participants to exchange of information on current initiatives and research activities. 3- Refine a framework and shortlist of indicators for sustainable diets and food systems. The final objective is to gather some recommendations with regard to the development of indicators of sustainable diets and food systems and identify a process for an improved list of indicators